Can savings induced by off-patent drugs balance the increase of pharmaceutical expense associated with the high ageing rate of the Italian population? (Italian Journal of Public Health, 2009)
Background: The predicted ageing rate of the Italian population is one of the highest worldwide and thiscondition is expected to produce a growing increase in pharmaceutical expenditure. The objective of thisstudy was to assess whether or not off-patent drugs could counterbalance the economic effects generated bythe aging of the Italian population in the next ten years.Methods: On the basis of the predicted ageing rate of the Italian population for the period 2008-2018, theaverage annual cumulative increase of pharmaceutical expenditure and potential savings generated by thefuture loss of patent coverage have been considered in order to identify the year of the Breakeven Point.Results: The economic effect induced by the progressive ageing of population produces an average of 0.94%cumulative increase in local pharmaceutical expenditure per year, corresponding to an incrementalpharmaceutical expenditure of about € 116 millions per year.A number of 509 brands (103 active substances) will lose their patent coverage in the next 10 years.Considering both the present legislation and a level of price reduction, after patent expiration, correspondingto 40%, it is predicted that the Breakeven Point will be achieved at the end of 2011.Conclusions: In this study, a long term balance between the predictable increase of pharmaceuticalexpenditure induced by the ageing of Italian population and savings produced by future off-patent drugs wasnot established. In order to assure the future sustainability of pharmaceutical expenditure, this studysupports the need for the development of new health policy strategies.
Keywords: off-patent drugs; population ageing; pharmaceutical expenditure